Spitting In Islamic Legal And Ethical Perspective: An Analysis Of Hadith Literature - Muzakkir (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2025)
This article examines the hadiths of the Prophet PBUH about the practice of spitting with the aim of analyzing the normative messages contained in them and their implications for the religious practices of Muslims. This study arose because the practice of spitting is often considered a purely biological act, even though in the hadith of the Prophet PBUH this behavior receives special attention, especially in the context of worship and the use of sacred spaces. This research is a qualitative research with a library research approach, with the main data sources in the form of primary hadith books and sharia hadith literature. Data analysis is carried out through a descriptive-analytical approach by examining hadiths related to the practice of spitting, then interpreting them textually and contextually. The results of the study show that the hadiths of the Prophet PBUH about spitting affirm the prohibition of spitting in mosques and towards the qibla as part of the formation of adab, respect for sacred spaces, and the cultivation of the values of cleanliness and social ethics. These hadiths are not repressive, but educational and proportionate, while still considering human reality. Therefore, the hadiths about the practice of spitting provide a normative foundation that is relevant in shaping civilized and benefit-oriented religious behavior. Abstrak Artikel ini mengkaji hadis-hadis Nabi SAW tentang praktik meludah dengan tujuan menganalisis pesan normatif yang terkandung di dalamnya serta implikasinya terhadap praktik keagamaan umat Islam. Kajian ini berangkat dari kenyataan bahwa praktik meludah sering dipandang sebagai tindakan biologis semata, padahal dalam hadis Nabi SAW perilaku tersebut mendapatkan perhatian khusus, terutama dalam konteks ibadah dan penggunaan ruang sakral. Penelitian ini merupakan penelitian kualitatif dengan pendekatan studi kepustakaan (library research), dengan sumber data utama berupa kitab-kitab hadis primer dan literatur syarḥ hadis. Analisis data dilakukan melalui pendekatan deskriptif-analitis dengan menelaah hadis-hadis yang berkaitan dengan praktik meludah, kemudian memaknainya secara tekstual dan kontekstual. Hasil penelitian menunjukkan bahwa hadis-hadis Nabi SAW tentang meludah menegaskan larangan meludah di masjid dan ke arah kiblat sebagai bagian dari pembentukan adab, penghormatan terhadap ruang sakral, serta penanaman nilai kebersihan dan etika sosial. Hadis-hadis tersebut tidak bersifat represif, melainkan edukatif dan proporsional, dengan tetap mempertimbangkan realitas manusiawi. Oleh karena itu, hadis-hadis tentang praktik meludah memberikan landasan normatif yang relevan dalam membentuk perilaku beragama yang beradab dan berorientasi pada kemaslahatan.